Detection of Sperm DNA Integrity and Some Immunological Aspects in Infertile Males - Mageed, Sarmad N.; Hamashareef, Shukur R.; Shallal, Ahmed F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Immunoinfertility caused by anti-sperm antibodies (ASAs) represents about 10–20% of infertility among couples, which interfere with sperm motility and ability to penetrate cervical mucus, sperm-oocyte binding, fertilization, and embryo development. In addition, deoxyribonucleic acid (DNA) damages are increasingly found with infertile cases affecting male reproduction potency and progeny. This study aims to assess the semen, presence of ASAs, and DNA fragmentation index in normozoospermic patients. A total number of 116 cases with an average age of 20–51 years old, and duration of infertility at 4.70 ± 2.77 are classified into 77 and 39 primary and secondary types of infertility, respectively. Mixed agglutination reaction test was used to estimate the ASAs in semen (direct method) and in seminal plasma and blood serum (indirect method), for both immunoglobulins IgG and IgA. Acridine orange test was used to detect DNA fragmentation index. The results showed a significant difference (P > 0.05) for those with a secondary type of infertility at means 24.37 and 31.48 for IgG, and 14.46 ± 1.76 and 6.86 ± 0.39 for IgA by both direct and indirect methods, respectively. The direct method showed a significant difference only for the sperm tail, while that for indirect method was in sperm mid-piece. The mean of DFI for all cases was 38.25 ± 2.08, at 41.61 ± 2.19 and 31.63 ± 4.29, for both primary and secondary cases, respectively. The percentage of ASAs revealed no significant difference with DFI, except in some parts of sperm.